2020
DOI: 10.1016/j.heliyon.2020.e03260
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative elemental analysis of selected potential anti-asthmatic medicinal plant taxa using EDXRF technique

Abstract: Qualitative elemental analysis was determined in various parts of potential anti-asthmatic medicinal plants using Energy Dispersive X-ray Fluorescence (EDXRF) spectrometer. X-ray beam was used to excite each sample and spectra were recorded with a high resolution Si(Li) detector. The data analysis was carried out by the nEXT software. Trace elements P, S, Cl, K, Ca, Mn, Fe, Cu, Zn, Se, Br, Rb and Sr were estimated and elemental concentrations were determined. The results of the present study compared with stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Levels of elemental concentration in a plant material may be attributable to mineral composition of the soil, habitat, different climatic and environmental conditions as well as human activities (51). Previous studies have reported high concentrations of potassium, calcium and magnesium in the seeds and fruit pulp of A. digitata (32), similar to the results of the present study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Levels of elemental concentration in a plant material may be attributable to mineral composition of the soil, habitat, different climatic and environmental conditions as well as human activities (51). Previous studies have reported high concentrations of potassium, calcium and magnesium in the seeds and fruit pulp of A. digitata (32), similar to the results of the present study.…”
Section: Discussionsupporting
confidence: 88%
“…This factor must be considered during collection for medicinal and nutritional purposes. Macro and micronutrients play important roles in disease management and prevention (51). They also provide consumers with essential minerals for optimum body function (52).…”
Section: Discussionmentioning
confidence: 99%
“…Essential elements are important for human health for the prevention and control of diseases. Several authors have estimated the element contents of medicinal plants (Pattar et al 2019;Jyothsna et al 2020). In the present study, all the studied plants revealed high level of essential elements such as Co, Cr and Ni.…”
Section: Discussionmentioning
confidence: 99%
“…Khan et al (2020) reported similar results for Verbascum thapsus. WHO recommended a daily intake of Ca at 450-1,200 mg/day (Jyothsna et al, 2020). Many important tasks such as regulation of body temperature, relaxation of muscles, and maintenance of electrical pulses are performed by K and Na.…”
Section: Macro-elementsmentioning
confidence: 99%